ANALISIS KARAKTERISTIK GAYA BELAJAR PESERTA DIDIK KELAS X5 IPA SMAN 1 SURAKARTA - Nisa Ulmah Mudah (Jurnal Muara Pendidikan, 2023)
Student in the school has different characteristic in receiving learning, including different learning styles. Learning styles owned by students affect the achievement of learning objectives. A teacher needs to understand the learning styles of students in order to create effective learning and differentiate. The purpose of this study was to determine the learning styles of students at SMAN 1 Surakarta. The subjects of this study were students of class X5 IPA SMAN 1 Surakarta. The research method used in this research is descriptive qualitative. Data collection in this study was carried out using observation instruments and questionnaires about learning styles. Observations were made and the learning style questionnaire was filled out by 36 students of class X5 IPA. Data from observations and questionnaires were analyzed using the percentage method and then described. The results of the analysis of learning styles show that there are 3 types of learning styles in class X5 IPA, namely visual, auditory, and kinesthetic learning styles. The tendency of the learning style of class X5 IPA students is visual learning style with a percentage of 64%.